Factor Mobility, Industrial Transfer and Industrial Carbon Emission: A Spatial Matching Perspective - Zheng, Xiao; Yu, Hong; Yang, Lin (Frontiers in Environmental Science, 2022)
This paper proposes a dynamic industrial transfer index for the first time to characterize the spatial matchability of factor mobility and industrial transfer, and then explores the correlation between factor mobility, industrial transfer and industrial carbon emission intensity by using panel data from 30 provinces in China during 2004 to 2019. The results show that China’s ability to reduce carbon emissions is improving, and the intensity of industrial carbon emission has dropped by 44.84%. In addition, there is an obvious spatial mismatch between factor mobility and industrial transfer. Specifically, production factors generally flow from high-carbon emission intensity areas to low-carbon emission intensity areas, while the direction of industrial transfer is generally opposite to that of factor mobility. And the empirical analysis finds that the interaction between factor mobility and industrial transfer will affect the carbon reduction. If the direction of capital mobility is the same as that of capital-intensive industries, it is unfavorable to the carbon emission reduction. While the carbon reduction effect will be enhanced if the directions of labor and technology mobility are consistent with those of labor-intensive and technology-intensive industrial transfer, respectively. Finally, based on the findings, some recommendations are provided for governments to formulate policies.